Reliability of screening tests for health-related problems among low-income elderly - Valéria Teresa Saraiva Lino; Margareth Crisóstomo Portela; Luiz Antônio Bastos Camacho; Nádia Cristina Pinheiro Rodrigues (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
Screening tests for health problems can identify elderly people who should undergo the Comprehensive Geriatric Assessment, enabling the planning of actions to prevent disability. The aim of this study was to analyze the inter-rater reliability (IRR) of self-assessment questions (SAQ) and performance tests (PT) recommended in Brazil, in a sample of low-income elderly people, through an exploratory study performed with 165 elderly assessed by two professionals on different days. IRR was evaluated using the intraclass correlation coefficient (ICC) for continuous variables and the kappa statistic for categorical ones. The IRR for the PT (muscle strength, mobility body mass index, vision) was excellent and presented ICC values greater than 0.75. By contrast, the IRR for SAQ (urinary incontinence, self-perceived health and hearing impairment) was intermediate. Only the fall-related item presented a good IRR. In this study single SAQ had poor reliability when compared to PT, suggesting the necessity of revision of subjective self-assessment items with low reproducibility before implementation.